Defining the Optimal Level of protection from Flying Devices - Vahram Nalchajyan (Bulletin of the "Gitastgh" Scientific-Educational Public Organization, 2026)
In this work, we analyzed mortgage loan repayment methods using financial mathematics tools and our own developments based on it. About ten years ago, the Government of the Republic of Armenia approved a new procedure for refunding income tax in an amount equal to the mortgage interest paid. On the surface, the borrower gains nothing: the interest payments represent profit for the lender, while the borrower repays the entire principal amount. However, this repayment does not happen all at once or upfront; rather, it occurs in installments over the entire term of the loan agreement. The study demonstrates that, initially, a sum significantly smaller than the mortgage amount is "set aside"; through subsequent investments of this sum, the principal will be repaid using the accumulated additional income. A comparative analysis reveals that, under the new regulations, the annuity repayment method is more advantageous for the borrower, particularly in cases involving high interest rates and/or long-term loans. Numerical examples are provided to substantiate these theoretical conclusions. Consequently, we have identified the highly flexible nature of mortgage lending, offering borrowers practical options and a wide range of possibilities.